Local Wisdom-Based Counseling: The Implementation of Sintuwu Maroso Values in Guidance and Counseling Services in Secondary Schools of Poso Regency - Nurul Izzah; Bau Ratu; Dhevy Puswiartika; Azam Arifyadi (AJIS: Academic Journal of Islamic Studies, 2026)
The crisis of social relationships and students' social-emotional development in school settings has become a critical issue that threatens the creation of harmonious and inclusive educational environments. The increasing prevalence of bullying, low levels of empathy, interpersonal conflicts, and declining social solidarity among students indicates that contemporary education must address not only academic challenges but also the broader crisis of social cohesion. Although numerous studies have examined character education and multicultural counseling, the integration of local cultural values as a relational foundation for guidance and counseling services remains underexplored. This study aims to examine the implementation of the values of Sintuwu Maroso in guidance and counseling services as a local wisdom-based approach to strengthening students' social relationships, empathy, and character development in schools. Employing a qualitative case study design, the research collected data through in-depth interviews, participant observation, and document analysis involving school counselors and students participating in guidance and counseling services in secondary schools across Poso Regency. The findings reveal that the implementation of Sintuwu Maroso values is reflected in three key dimensions: (1) strengthening interpersonal relationships through empathetic communication and mutual respect; (2) fostering social solidarity through collaboration, peer support, and peaceful conflict resolution; and (3) creating a harmonious and inclusive school environment that sustainably promotes students' social-emotional development. Furthermore, the study demonstrates that the values of Sintuwu Maroso function not only as a cultural identity of the Pamona community but also as an effective social mechanism for developing humanistic, contextual, and relationship-oriented guidance and counseling services in schools. The study recommends strengthening local wisdom-based guidance and counseling services through collaborative partnerships among schools, families, and local communities to enhance students' character, empathy, and social cohesion within multicultural educational settings.